A heterogeneous magnetic plastic-derived carbon catalyst and its preparation method and application
By developing a method of synergistic use of heterogeneous magnetic plastic-derived carbon catalysts and potassium persulfate, the problem of difficulty in removing organic phosphorus pesticides in the water environment is solved, efficient organic phosphorus removal effect is achieved, and the resource utilization of plastic solid waste is promoted.
Patent Information
- Application Number
- CN202311280328.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The prior art is difficult to efficiently remove organophosphorus pesticides in water environments, especially malathion, and the traditional advanced oxidation method of persulfate is relatively low.
A heterogeneous magnetic plastic derived carbon catalyst was developed, and the waste PET plastic was prepared by pyrolysis and impregnation, combined with ferrate-supported iron, forming a catalyst with the ability to activate persulfate, and used in conjunction with potassium persulfate to improve the removal efficiency of organophosphorus.
The removal effect of persulfate on organic phosphorus has been significantly improved, the removal rate of malathion reaches 73.56% to 100%, and the resource utilization of plastic solid waste is achieved, which is low in cost and has a wide range of application prospects.
Smart Images

Figure CN117463335B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic resource processing, and in particular to a heterogeneous magnetic plastic-derived carbon catalyst and a preparation method and application thereof. Background Art
[0002] Plastics are widely found in food packaging, medical devices, construction, transportation, furniture, electrical and electronic equipment, and have excellent flexibility, corrosion resistance, high strength-to-weight ratio, good processability, and low manufacturing cost. However, the rapid growth of plastic production coupled with improper management has generated a large amount of plastic waste in various environmental fields. Plastic waste has become a serious environmental problem and has attracted increasing attention. Various treatment technologies have been developed to remediate this waste. Traditional disposal methods are through direct landfill or incineration, both of which lead to serious environmental pollution. Therefore, alternative methods to convert plastic waste into value-added substances such as fuels, carbon-based materials, and fine chemicals have received increasing attention. Among them, converting plastic waste into carbon-based functional materials is particularly attractive, due to the practical applications of plastic waste-derived carbon materials in the field of green energy and sustainable environmental practices. How to change the properties of plastic waste, realize the resource utilization of plastic-derived carbon, and develop functional products with added value are key issues in properly solving the treatment and disposal of plastic pollution.
[0003] Activated carbon is a carbonaceous material with a well-developed porous structure and surface chemistry. These properties of activated carbon depend on the starting material and its preparation method, including the activator and the operating conditions. PET seems to be an excellent candidate for the preparation of activated carbon precursors, mainly because of its high carbon content and negligible inorganic content in its chemical composition. Carbonization technology is an emerging thermal treatment technology for solid waste treatment in recent years. It mainly forms partially or completely carbonized heterogeneous materials by thermally converting organic matter under anaerobic conditions. Activated carbon can be widely used in agriculture, carbon fixation, wastewater treatment and other fields. As an adsorbent, activated carbon can adsorb impurities, filter and remove bacteria from rainwater, and adsorb and remove antibiotics and synthetic organic matter. As a catalyst, it can activate strong oxidants to produce active oxygen to degrade pollutants in water.
[0004] Organophosphate insecticides account for about 40% of the total amount of pesticides applied worldwide, among which malathion (MTN) is the most widely used insecticide, accounting for about 32-44% of all organophosphate insecticides used. It is also known as thiol, madipine and carbonylphosphorus, and is a non-systemic, broad-spectrum organophosphate pesticide used to protect various crops from leafhoppers, files, scales, aphids, cornworms, mites and other weeds. It can cause serious health damage by effectively blocking acetylcholinesterase, a key enzyme in nerve function. The effects of MTN may interfere with the endocrine and reproductive systems of mammals and cause cancer tumors, childhood leukemia, anemia and kidney failure. In addition, it can effectively respond to several chemicals to produce more destructive malathion compounds at an intensity of more than 100 times under sunlight. Due to its high consumption and high physicochemical stability, MTN has caused widespread pollution in natural water resources, and it is difficult for the existing physical, chemical and biological treatment units of sewage treatment plants to effectively remove such toxic and recalcitrant substances. Therefore, there is an urgent need to find a new way to effectively remove organophosphorus pesticides from water environments.
[0005] The persulfate-based advanced oxidation process has a great impact on the degradation of organic phosphorus in urban sewage and groundwater due to its powerful free radical-driven process and direct electron transfer, which has attracted widespread attention. However, the efficiency of removing organic phosphorus using persulfate alone is generally maintained between 30% and 40%. Therefore, how to efficiently activate persulfate to remove organic pollutants in water has become a topic of in-depth research for many workers. Summary of the invention
[0006] The purpose of the present invention is to provide a heterogeneous magnetic plastic-derived carbon catalyst and a preparation method and application thereof, so as to solve the problems existing in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solution: a heterogeneous magnetic plastic-derived carbon catalyst, the preparation method of which comprises the following steps:
[0008] 1) After pretreatment, the plastic is soaked in a NaOH solution, washed and dried, and then placed in a tubular furnace for pyrolysis to obtain initial activated carbon AC.
[0009] 2) The obtained initial activated carbon AC is mixed with a ferrate solution, loaded with iron by an impregnation method, and then dried, and then placed in a tubular furnace for pyrolysis to obtain a heterogeneous magnetic plastic-derived carbon catalyst.
[0010] Furthermore, in the above-mentioned heterogeneous magnetic plastic-derived carbon catalyst, in step 1), the plastic is waste PET plastic.
[0011] Furthermore, in the above-mentioned heterogeneous magnetic plastic-derived carbon catalyst, in step 1), the conditions for pyrolysis in a tubular furnace are: under a nitrogen atmosphere, the nitrogen flow rate is 200 mL / min, the pyrolysis temperature is 700°C, the heating rate is 10°C / min, and the pyrolysis time is 60 min.
[0012] Furthermore, in the above-mentioned heterogeneous magnetic plastic-derived carbon catalyst, in step 2), the ferrate is potassium ferrate.
[0013] Furthermore, in the above-mentioned heterogeneous magnetic plastic-derived carbon catalyst, the concentration of potassium ferrate is 0.01-0.2 mol / L, and the feed ratio of initial activated carbon AC to potassium ferrate is: 1 g: 30-70 mL.
[0014] Furthermore, in the above-mentioned heterogeneous magnetic plastic-derived carbon catalyst, in step 2), the conditions for pyrolysis in a tubular furnace are: under a nitrogen atmosphere, the nitrogen flow rate is 200 mL / min, the pyrolysis temperature is 700-1000°C, the heating rate is 10°C / min, and the pyrolysis time is 120 min.
[0015] The invention provides an application of a heterogeneous magnetic plastic-derived carbon catalyst in cooperation with persulfate in the degradation of organophosphorus pesticides.
[0016] Furthermore, the persulfate is potassium hydrogen persulfate.
[0017] Furthermore, the potassium persulfate is potassium peroxymonosulfate.
[0018] Furthermore, the organophosphorus pesticide is malathion.
[0019] Furthermore, the method is as follows: a heterogeneous magnetic plastic-derived carbon catalyst and potassium permonosulfate are added to malathion wastewater at the same time, and the reaction is carried out in a mechanical stirrer at a rotation speed of 300 rpm under normal temperature conditions, and the reaction time is 15 minutes; the addition amount of the heterogeneous magnetic plastic-derived carbon catalyst is 50-200 mg / L, and the addition amount of potassium permonosulfate is 0.1-0.7 mmol / L.
[0020] The beneficial effects of the present invention are:
[0021] 1. The heterogeneous magnetic plastic-derived carbon catalyst prepared by the present invention is used as a carbon material, and its surface catalytic sites (such as oxygen-containing functional groups, defects, metal compounds, etc.) can activate persulfate, thereby promoting the generation of active species such as sulfate free radicals, hydroxyl free radicals, superoxide free radicals and singlet oxygen, and significantly improving the removal effect of persulfate on organic phosphorus.
[0022] 2. The heterogeneous magnetic plastic-derived carbon catalyst prepared by the present invention is used as a carbon material, with waste plastic as the main raw material, thus realizing the resource utilization of plastic solid waste. The preparation method is simple and easy with low cost, and has great application prospects in the removal of difficult-to-degrade organic pollutants such as organophosphorus.
[0023] 3. PET is a plastic resin composed of ethylene glycol and terephthalic acid as monomer units. It is commonly used for packaging and storage of various consumables. PET is also relevant as an environmentally redundant solid waste. Scattered PET garbage deteriorates the quality of soil, water and air through suffocation, toxin leaching and carcinogen emissions during combustion. Therefore, the strategy of converting PET waste into functional materials can provide a respite for the environment and reduce the economic burden of waste disposal in any country in the world. The present invention can effectively utilize simple impregnation pyrolysis to prepare heterogeneous magnetic plastic-derived carbon catalysts, which not only provides a way to recycle waste plastics, but also provides a low-cost and efficient catalyst that can efficiently remove organic phosphorus in wastewater, which is of great significance for optimizing the treatment of difficult-to-degrade organic pollutants and achieving energy conservation and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a diagram showing the effect of removing malathion by activating persulfate with the heterogeneous magnetic plastic-derived carbon catalyst prepared in Examples 1 to 4 of the present invention.
[0026] Figure 2 This is a diagram showing the removal effect of different catalysts on malathion.
[0027] Figure 3 This is a diagram showing the recycling effect of the heterogeneous magnetic plastic-derived carbon catalyst prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention belongs. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0032] Example 1
[0033] The heterogeneous magnetic plastic-derived carbon catalyst is prepared as follows:
[0034] 1. Preparation of initial activated carbon AC:
[0035] The discarded PET plastic bottles were cleaned and cut into small pieces. The fragments were ultrasonically cleaned again and dried. The dried fragments were added to a 1mol / L NaOH solution and soaked for 24 hours. After soaking and modification, they were cleaned and dried, and placed in a tubular furnace for pyrolysis. The pyrolysis conditions were: under a nitrogen atmosphere, a nitrogen flow rate of 200mL / min, a pyrolysis temperature of 700℃, a heating rate of 10℃ / min, and a pyrolysis time of 60min; the initial activated carbon AC was obtained, and the obtained AC was crushed and passed through a 100-mesh sieve.
[0036] 2. Preparation of heterogeneous magnetic plastic-derived carbon catalyst:
[0037] 1g AC was added to 50mL of 0.1mol / L potassium ferrate solution and impregnated for 8h. After loading iron by impregnation, AC was placed in a 100℃ oven for drying. AC was then placed in a tubular furnace for pyrolysis. The pyrolysis conditions were: under nitrogen atmosphere, nitrogen flow rate was 200mL / min, pyrolysis temperature was 700℃, heating rate was 10℃ / min, pyrolysis time was 120min, and a heterogeneous magnetic plastic-derived carbon catalyst was obtained, which was recorded as FAC700.
[0038] Example 2
[0039] The heterogeneous magnetic plastic-derived carbon catalyst is prepared as follows:
[0040] 1. Preparation of initial activated carbon AC: same as Example 1
[0041] 2. Preparation of heterogeneous magnetic plastic-derived carbon catalyst:
[0042] 1g AC was added to 50mL of 0.1mol / L potassium ferrate solution and impregnated for 8h. After loading iron by impregnation, AC was placed in a 100℃ oven for drying. AC was then placed in a tubular furnace for pyrolysis. The pyrolysis conditions were: under nitrogen atmosphere, nitrogen flow rate was 200mL / min, pyrolysis temperature was 800℃, heating rate was 10℃ / min, pyrolysis time was 120min, and a heterogeneous magnetic plastic-derived carbon catalyst was obtained, which was recorded as FAC800.
[0043] Example 3
[0044] The heterogeneous magnetic plastic-derived carbon catalyst is prepared as follows:
[0045] 1. Preparation of initial activated carbon AC: same as Example 1
[0046] 2. Preparation of heterogeneous magnetic plastic-derived carbon catalyst:
[0047] 1g AC was added to 50mL of 0.1mol / L potassium ferrate solution and impregnated for 8h. After loading iron by impregnation, AC was placed in a 100℃ oven for drying. AC was then placed in a tubular furnace for pyrolysis. The pyrolysis conditions were: under nitrogen atmosphere, nitrogen flow rate was 200mL / min, pyrolysis temperature was 900℃, heating rate was 10℃ / min, pyrolysis time was 120min, and a heterogeneous magnetic plastic-derived carbon catalyst was obtained, which was recorded as FAC900.
[0048] Example 4
[0049] The heterogeneous magnetic plastic-derived carbon catalyst is prepared as follows:
[0050] 1. Preparation of initial activated carbon AC: same as Example 1
[0051] 2. Preparation of heterogeneous magnetic plastic-derived carbon catalyst:
[0052] 1g AC was added to 50mL of 0.1mol / L potassium ferrate solution and impregnated for 8h. After loading iron by impregnation, AC was placed in a 100℃ oven for drying. AC was then placed in a tubular furnace for pyrolysis. The pyrolysis conditions were: under nitrogen atmosphere, nitrogen flow rate was 200mL / min, pyrolysis temperature was 1000℃, heating rate was 10℃ / min, pyrolysis time was 120min, and a heterogeneous magnetic plastic-derived carbon catalyst was obtained, which was recorded as FAC1000.
[0053] Example 5 Application
[0054] (I) Effect of FAC prepared at different pyrolysis temperatures on the degradation of malathion by potassium peroxymonosulfate
[0055] Method: The heterogeneous magnetic plastic derived carbon catalyst and potassium peroxymonosulfate prepared in Examples 1 to 4 were added to the malathion wastewater with an initial concentration of 10 mg / L, respectively, and the reaction was carried out in a mechanical stirrer at a speed of 300 rpm at room temperature for 15 minutes. The dosage of the heterogeneous magnetic plastic derived carbon catalyst was 0.1 g / L, and the dosage of potassium peroxymonosulfate was 0.5 mmol / L.
[0056] Test method: Take 1mL of the reaction sample at a certain time interval and add 25μL of 200mmol / L sodium thiosulfate, filter through a 0.22μm filter membrane and put it into a liquid phase vial for determination using high performance liquid chromatography. Liquid phase conditions: The stationary phase is a C18 column, the injection volume is 10μL each time, acetonitrile: ultrapure water = 7:3 as the mobile phase and feed at a flow rate of 1.0mL / min, the wavelength of the UV detector is set to 202nm, and the determination is carried out at 30℃. The removal rate of organic phosphorus is calculated. The results are as follows: Figure 1 .
[0057] from Figure 1 It can be seen that the heterogeneous magnetic plastic-derived carbon catalyst prepared in Examples 1 to 4 of the present invention, combined with potassium permonosulfate (PMS), can make the degradation rates of malathion be 73.56%, 86.67%, 100% and 100% respectively.
[0058] (II) Effects of different catalysts on the degradation of malathion by potassium peroxymonosulfate
[0059] Method: Different catalysts and potassium permonosulfate were added to the malathion wastewater with an initial concentration of 10 mg / L, and the reaction was carried out in a mechanical stirrer at a speed of 300 rpm under normal temperature conditions for 15 min. The dosage of the catalyst was 0.1 g / L, and the dosage of potassium permonosulfate was 0.5 mmol / L. The catalysts were selected from potassium permonosulfate alone, AC alone, FAC900 alone, and FAC900 and potassium permonosulfate at the same time.
[0060] Test method: Same as (1), the results are as follows Figure 2 .
[0061] from Figure 2 It can be seen that FAC and AC reached saturation adsorption of malathion in 5 minutes, and the removal rates were 41.52% and 19.51% respectively. When potassium persulfate was used alone within 15 minutes, the removal rate was only 62.93%. The simultaneous use of FAC and potassium persulfate resulted in a final malathion removal rate of 100%.
[0062] (III) FAC reuse
[0063] Taking FAC900 as an example, after the degradation reaction is completed, FAC is recovered by filtration, ultrasonically cleaned with ultrapure water and dried, and then used in the second round of activation of potassium persulfate to degrade malathion. The experimental steps are the same as (I), and the cycle experiment is repeated 4 times to determine the reuse effect of the heterogeneous magnetic plastic-derived carbon catalyst prepared in Example 1 of the present invention. The results are as follows: Figure 3 .
[0064] from Figure 3 It can be seen that the removal rates of malathion in the first, second, third and fourth rounds of experiments were 100%, 92.18%, 82.69% and 79.84%, respectively. This is because after repeated reuse, the adsorption sites of FAC itself are close to saturation, which reduces the removal efficiency of malathion by adsorption. At the same time, the concentration of iron ions leached by FAC decreases, which also reduces the activation capacity of potassium permonosulfate. In the four rounds of experiments, the removal rate of malathion is higher than the removal rate of potassium permonosulfate and FAC alone in (II), indicating that the reuse effect of FAC is good and the performance is stable.
[0065] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An application of a heterogeneous magnetic plastic-derived carbon catalyst in synergistic with persulfate in the degradation of malathion, characterized in that: The method for preparing a heterogeneous magnetic plastic-derived carbon catalyst comprises the following steps: 1) After pretreatment, PET plastic was soaked in NaOH solution, washed and dried, and then placed in a tubular furnace for pyrolysis to obtain initial activated carbon AC; the pyrolysis conditions were: under nitrogen atmosphere, nitrogen flow rate was 200 mL / min, pyrolysis temperature was 700 °C, heating rate was 10 °C / min, and pyrolysis time was 60 min; 2) The obtained initial activated carbon AC is mixed with potassium ferrate solution, loaded with iron by impregnation method and then dried, and then placed in a tubular furnace for pyrolysis to obtain a heterogeneous magnetic plastic-derived carbon catalyst.
2. The use according to claim 1, characterized in that: The concentration of potassium ferrate is 0.01-0.2 mol / L, and the initial feed ratio of activated carbon AC to potassium ferrate is: 1 g: 30-70 mL.
3. The use according to claim 1, characterized in that: In step 2), the conditions for pyrolysis in a tubular furnace are: under a nitrogen atmosphere, a nitrogen flow rate of 200 mL / min, a pyrolysis temperature of 700-1000°C, a heating rate of 10°C / min, and a pyrolysis time of 120 min.
4. The use according to claim 1, characterized in that: The persulfate is potassium persulfate.
5. The use according to claim 1, characterized in that: The dosage of the heterogeneous magnetic plastic-derived carbon catalyst is 50-200 mg / L, and the dosage of the persulfate is 0.1-0.7 mmol / L.
Citation Information
Patent Citations
Method for preparing activated carbon with high specific surface area by waste PET mineral water bottles
CN101708843A